Observational study protocol: the faecal microbiome in the acute stage of new-onset paediatric type 1 diabetes in an Irish cohort - Eugene Dempsey; Catherine Stanton; Paul Ross; Colin Patrick Hawkes; Aonghus Lavelle; Carol-Anne O’Shea; Elaine Catherine Kennedy; Fiona Catherine Ross (BMJ Open)
Introduction Type 1 diabetes (T1D) is an autoimmune-mediated disorder caused by the destruction of pancreatic beta cells. Although there is an underlying genetic predisposition to developing T1D, the trigger is multifactorial and likely includes environmental factors. The intestinal microbiome has been identified as one such factor. Previous studies have illustrated differences in the microbiota of people with T1D compared with healthy controls. This study aims to describe the evolution of the microbiome and metabolome during the first year of clinical T1D, or stage 3 T1D diagnosis, and investigate whether there are differences in the microbiome and metabolome of children who present with and without diabetic ketoacidosis. The study will also explore possible associations between the microbiome, metabolome, glycaemic control and beta cell reserve.Methods and analysis This prospective cohort study will include children with newly diagnosed T1D and sibling controls (n=100, males and females) and their faecal microbiome will be characterised using shotgun metagenomic sequencing at multiple time points during the first year of diagnosis. We will develop a microbial culture biobank based on culturomic studies of stool samples from the healthy controls that will support future investigation. Metabolomic analysis will aim to identify additional biomarkers which may be involved in disease presentation and progression. Through this initial exploratory study, we aim to identify specific microbial biomarkers which may be used as future interventional targets throughout the various stages of T1D progression.Ethics and dissemination This study has been approved by the Clinical Research Ethics Committee of the Cork Teaching Hospitals. Study results will be available to patients with T1D and their families, carers, support networks and microbiome societies and other researchers.Trial registration number The clinicaltrials.gov registration number for this trial is NCT06157736.